Production and Marketed Surplus of Crops in Uganda, 1999-2006 - Kraybill, David; Bashaasha, Bernard; Betz, Michael (International Food Policy Research Institute, 2012)
Recent trends in Ugandan agriculture indicate output is increasing for most crops but at a declining rate. The pervasive decline in output per unit of input (factor productivity) threatens the economic well-being and food security of producers and consumers of food in Uganda. Many households are both agricultural producers and consumers and have little access to other sources of livelihood (UBOS 2007). For these households, the declining productivity is particularly serious. Evidence is presented in this paper that improved agricultural inputs and extension information contribute to higher yields, but rates of adoption of improved agricultural inputs are low and many farmers have no access to extension services. Despite the low productivity, marketed surplus as a share of total agricultural output has increased for many food crops (PMA 2007).